Medicinal and Aromatic Plants of Punjab State and the Plan for their Development - Singh, Jagjit (Indian Forester, 1962)
The veritable climatic character of Punjab State is outlined. The occurrence of various medicinal and aromatic plants, present method of exploitation and the quantities exploited during 1960-61 from Kulu area are discussed giving the result of the present system of working. For the development of such resources of the State two suggestions, namely (1) Systematic exploitation of existing resources and (2) Cultivation of medicinal and aromatic plants have been advanced. The result of trials on various plants carried out during the last 10 years in Forest Research Nurseries are summarised.